Implementasi Jaringan VoIP Uji Coba Pada Satpam di Perum KSB Desa Sukaragam Kecamatan Serang Baru Bekasi - Effendi, Muhammad Makmun; Yunus, Imsal (DPPM Universitas Pelita Bangsa, 2024)
Perum KSB, Sukaragam Village, Serang Baru District, Bekasi, has security guards spread across several telecommunications security areas in Perum KSB, still using PABX (Private Automatic Brach Exchange). telephone technology where every analog telephone device in the room is connected using a cable to PABX device. This of course sometimes causes problems if used for a long period of time, starting from maintenance side and inaccessibility of mobility between security guards regarding this use analog telephone device. Therefore, modern technology is needed, namely using asterisk-based VoIP (Voice over Internet Protocol) technology designed and built using Ansible AWX (Ansible Web eXecutable) tool as a server to automate every process. Communication media for analog telephone devices will be replaced by using Zoiper software as a softphone that is installed on every security guard's smartphone device.